2016
DOI: 10.1002/hed.24523
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial schwannoma in the carotid space: A retrospective review of 91 cases

Abstract: In the carotid space, schwannomas of the vagus nerve are usually located below the hyoid bone, whereas schwannomas of the sympathetic nerve more commonly arise from the suprahyoid compartment. Accurate preoperative diagnosis and the intracapsular enucleation surgical approach decreased the incidence of postoperative morbidity. © 2016 Wiley Periodicals, Head Neck 39: 42-47, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
3
36
2
Order By: Relevance
“…2,3,7,15 However, in 28 cases with satisfactory specimens in the present study, the sensitivity was 64.3% (18/28), which represents an acceptable diagnostic performance. These results were similar to those of previous studies that evaluated FNAC for the diagnosis of schwannoma, which reported unsatisfactory specimen rates of 36%-50% and sensitivity rates of 0%-40%.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…2,3,7,15 However, in 28 cases with satisfactory specimens in the present study, the sensitivity was 64.3% (18/28), which represents an acceptable diagnostic performance. These results were similar to those of previous studies that evaluated FNAC for the diagnosis of schwannoma, which reported unsatisfactory specimen rates of 36%-50% and sensitivity rates of 0%-40%.…”
Section: Discussioncontrasting
confidence: 54%
“…These results were similar to those of previous studies that evaluated FNAC for the diagnosis of schwannoma, which reported unsatisfactory specimen rates of 36%-50% and sensitivity rates of 0%-40%. 2,3,7,15 However, in 28 cases with satisfactory specimens in the present study, the sensitivity was 64.3% (18/28), which represents an acceptable diagnostic performance. Therefore, we posit that the challenge of diagnosing schwannoma using FNAC is primarily attributed to the difficulty of harvesting satisfactory specimens and not to the evaluation of microscopic findings per se.…”
Section: Discussioncontrasting
confidence: 54%
“…Diagnostic performance of ultrasound‐guided FNAC for PPS tumors was shown to be relatively low . Moreover, no studies have shown the usefulness of FNAC in cervical schwannomas, and the accuracy of FNAC has been reported to be 20.0%‐30.3% . FNAC is likely not essential in cases of suspected schwannoma, because cell sampling per se is not only very difficult due to strong intercellular binding but also carries the risk of injury of the involved nerve.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the concept of intracapsular enucleation, which is based on technical ingenuity, has become popular because it can potentially preserve neural function. Application of intracapsular enucleation for cervical schwannomas has been reported to result in a decrease in the incidence of postoperative neurological deficits in the nerve of origin . However, no study performed to date has investigated differences in the efficacy of extirpation methods, including intracapsular enucleation, in terms of the occurrence of postoperative neurological complications exclusively in PPS schwannomas.…”
Section: Introductionmentioning
confidence: 99%
“…11,[26][27][28][29][30][31][32][33][34][35][36][37] Benign lesions are suitable for extracapsular enucleation or close-margin dissection (also called extracapsular dissection) according to the presence of a capsule and tendency to local invasion. 11,[26][27][28][29][30][31][32][33][34][35][36][37] Benign lesions are suitable for extracapsular enucleation or close-margin dissection (also called extracapsular dissection) according to the presence of a capsule and tendency to local invasion.…”
Section: Discussionmentioning
confidence: 99%